2017
DOI: 10.1016/j.circir.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Estudio prospectivo y randomizado sobre inmunonutrición oral preoperatoria en pacientes intervenidos por cáncer colorrectal: estancia hospitalaria y costos sanitarios

Abstract: NOT IN patients suffered infectious complications more frequently than YES IN, with significant results in the subgroup of patients with rectal cancer. The total hospital stay and costs were slightly higher in the group not supplemented, doubling in each category significantly (YES IN, NOT IN, colon and rectal cancer), when infectious complications were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…After reviewing scientific studies, we found Spanish papers that refer to these findings. The study by Barreiro et al shows a reduction in SSI from 1.9% to 0.8% 21 and Manzanares et al reported a reduction in SSI from 40% to 33% 22 .…”
Section: Discussionmentioning
confidence: 93%
“…After reviewing scientific studies, we found Spanish papers that refer to these findings. The study by Barreiro et al shows a reduction in SSI from 1.9% to 0.8% 21 and Manzanares et al reported a reduction in SSI from 40% to 33% 22 .…”
Section: Discussionmentioning
confidence: 93%
“…After reviewing scientific studies, we found Spanish papers that refer to these findings. The study by Barreiro et al shows a reduction in SSI from 1.9% to 0.8% 21 and Manzanares et al reported a reduction in SSI from 40% to 33% 22 .…”
Section: Discussionmentioning
confidence: 93%